A modified and shaped copper-plated steel fiber, preparation method and application thereof
By plating steel fibers, shaping structure and immersing the phosphoric acid solution, the phosphate layer is formed, which solves the problems of unstable bone grip strength, complex processing and high cost of UHPC steel fibers, and achieves higher adhesion and tensile strength.
Patent Information
- Application Number
- CN202410143177.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-01
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-02-01
AI Technical Summary
The prior art has problems such as poor stability, complex processing and high cost in improving the bone grip of UHPC steel fibers, which are difficult to meet engineering needs.
By plating the steel fibers with copper and shaping the structure, the middle is wavy and the ends are bifurcated, and soaking them in a 65% phosphoric acid solution to form a phosphate layer to improve adhesion.
It improves the bonding force and tensile strength between steel fiber and concrete, enhances the crack resistance and durability of UHPC, while simplifies the processing process and reduces costs.
Smart Images

Figure CN117966224B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic materials for mining, and specifically relates to a modified and shaped copper-plated steel fiber, a preparation method and application thereof. Background Art
[0002] UHPC (Ultra-High Performance Concrete) is a new type of high-performance concrete with the advantages of high strength, high durability and high crack resistance. UHPC has been widely used in industrial buildings, bridges, tunnels and marine engineering. Although UHPC performs well in compression, its tensile performance is relatively low. Adding an appropriate amount of steel fiber to UHPC can significantly improve the tensile strength and toughness of UHPC, thereby increasing the bearing capacity and seismic performance of the structure. Steel fiber in UHPC can effectively resist the development of cracks, reduce the width and number of cracks, and improve the overall performance and durability of the material. This is especially important for structures that need to be used for a long time and withstand load changes. The addition of steel fiber can effectively reduce microcracks in UHPC, improve the material's impermeability and durability, reduce the penetration of moisture and gas, and extend the service life of the structure.
[0003] Steel fiber is a thin steel wire with a circular cross section. Steel fiber is useful for transmitting and distributing stress in concrete. Because steel fiber itself has a high tensile strength, adding it to concrete helps anchor the steel fiber to the concrete, effectively strengthening the adhesion of the concrete, making the concrete stronger and tougher, and not easy to be cracked. However, in actual applications, the grip between steel fiber and concrete is insufficient, which easily leads to falling off, making the performance of UHPC not fully utilized.
[0004] At present, some methods have been proposed to improve the bone holding strength of UHPC steel fibers, such as surface treatment, chemical treatment, roughening treatment, binder treatment, and optimization of concrete formula. Surface treatment is to enhance the bonding ability between steel fibers and concrete by surface treatment of steel fibers. Common surface treatment methods include acid washing, alkali washing, phosphating, etc. These treatments can remove oxides and pollutants on the surface of steel fibers, improve their surface roughness and activity, and thus increase their bonding ability with concrete. Chemical treatment is to use chemical modifiers to improve the bonding ability of UHPC steel fibers. For example, organic adhesives or polymer modifiers can be used to coat the surface of steel fibers to form a film with bonding enhancement effect. This film can increase the friction and adhesion between steel fibers and concrete and improve bone holding strength. Roughening treatment is to increase the surface roughness of steel fibers by adding microscopic concave-convex structures to the surface of steel fibers, thereby enhancing the bonding ability with concrete. Common roughening treatment methods include sandblasting, cutting and stretching, etc. These treatment methods can increase the mechanical anchoring effect between steel fibers and concrete and improve bone holding strength. Binder treatment is to add a certain proportion of binder, such as high-performance adhesive or cement-based cementitious materials, to UHPC to enhance the bonding ability between steel fiber and concrete. These binders can fill the microscopic gaps between steel fiber and concrete to form a tighter bonding interface and improve bone holding strength. Optimizing the concrete formula is to enhance the bonding ability between concrete and steel fiber by adjusting the UHPC formula, including the use of admixtures such as fly ash and silica, as well as the water-cement ratio, the type and proportion of cementitious materials. By optimizing the formula, the pore structure and micromechanical properties of concrete can be improved, and the bone holding strength can be improved.
[0005] The above methods still have some problems in improving the bone-holding strength of UHPC steel fibers, including: (1) Unstable bone-holding strength: The existing methods often cannot guarantee consistency and stability when improving the bone-holding strength, resulting in differences in the bonding properties between steel fibers and concrete, which is difficult to meet engineering needs. (2) Complex processing: The surface treatment, chemical treatment or heat treatment processes involved in the existing methods are cumbersome and time-consuming, and require additional equipment and material support, which increases the cost and cycle of the project. (3) High cost: The materials and equipment used in the existing methods are expensive, which is not economical for large-scale engineering applications, limiting their promotion and application scope. Therefore, it is necessary to propose a simpler, more economical and effective method to improve the bone-holding strength of UHPC steel fibers. Summary of the invention
[0006] The present invention provides a method for preparing a modified and shaped copper-plated steel fiber, the steps of which are as follows:
[0007] The steel fiber is copper plated; the copper plated steel fiber is then structurally shaped so that the middle part is wavy and the two ends are forked; the shaped copper plated steel fiber is then immersed in a phosphoric acid solution, and after the immersion is completed, it is dried to obtain a modified shaped copper plated steel fiber.
[0008] In the above preparation method, the middle part of the copper-plated steel fiber can be made to present a wavy shape by mechanical or hydraulic processing; welding, cold forging or hot forging can be used to form a bifurcated structure at both ends of the wavy copper-plated steel fiber.
[0009] In the above preparation method, the concentration of the phosphoric acid solution is selected from 10 to 85%, preferably 65%.
[0010] In the above preparation method, the immersion time is based on sufficient reaction between phosphoric acid and the surface of the copper-plated steel fiber, and can also be specifically selected from 1 to 3 months; preferably 2 months.
[0011] The invention provides a modified and shaped copper-plated steel fiber prepared by the method.
[0012] The present invention provides the use of the modified shaped copper-plated steel fiber in the preparation of high-grip strength UHPC concrete.
[0013] The present invention provides a UHPC concrete, which is composed of the following components in parts by mass:
[0014] 40-80 parts of cement, 2-8 parts of modified shaped copper-plated steel fiber, 2-7 parts of kaolin, 2-10 parts of silica fume, 30-50 parts of quartz sand, 0.1-0.4 parts of polycarboxylic acid water reducer, and 0.1-0.6 parts of defoaming agent.
[0015] In a specific embodiment, the UHPC concrete is composed of the following components in parts by mass:
[0016] 60 parts of cement, 5 parts of modified plastic copper-plated steel fiber, 5 parts of kaolin, 4 parts of silica fume, 42 parts of quartz sand, 0.2 parts of polycarboxylic acid water reducer, and 0.2 parts of defoaming agent.
[0017] In the above-mentioned UHPC concrete components, the cement is selected from P.O52.5 silicate cement; the length of the copper-plated steel fiber (before shaping) is selected from 10 to 25 mm, preferably 12 to 15 mm; the particle size of the kaolin is selected from 300 to 500 meshes, preferably 325 meshes; the silica fume is selected from nano-grade silica fume; the quartz sand is composed of the following three particle sizes of quartz sand: 10 parts of 10-20 mesh quartz sand, 16 parts of 20-40 mesh quartz sand, and 16 parts of 40-70 mesh quartz sand; the polycarboxylate water reducer is selected from one or more of carboxylic acid-type polycarboxylate water reducer, sulfate-type polycarboxylate water reducer, and hydroxyphosphate-type polycarboxylate water reducer, preferably a carboxylic acid-type polycarboxylate water reducer; the defoamer is selected from one or more of an organosilicon defoamer, a nonionic surfactant defoamer, and an anionic surfactant defoamer, preferably an organosilicon defoamer.
[0018] The beneficial effects of the present invention are:
[0019] The present invention first copper-plates the steel fibers, and then structurally shapes the copper-plate steel fibers so that the copper-plate steel fibers are wavy in the middle and forked at both ends, thereby increasing the bonding force and tensile strength between the copper-plate steel fibers and concrete. Then, the present invention soaks the copper-plate steel fibers in a phosphoric acid solution, performs surface treatment on the copper-plate steel fibers, optimizes the surface morphology of the copper-plate steel fibers, improves the bonding performance of the contact between the steel fibers and the UHPC concrete, improves the gripping ability of the steel fibers and the concrete, and facilitates the dispersion of the steel fibers in the concrete, thereby improving the economy and practicality of the steel fibers. After the above-mentioned modification, the bonding performance between the steel fibers and the UHPC concrete is improved, thereby improving the consistency and stability of the gripping force. At the same time, the processing method of the present invention is simple and easy to operate, saves time and cost, and improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Diagram of shaping the copper-coated steel fiber structure. DETAILED DESCRIPTION
[0021] In the present invention, the steel fiber needs to be copper-plated. To simplify the experimental steps, copper-plated steel fibers can be directly purchased through commercial channels to replace the copper-plating process of the steel fibers. The copper-plated steel fibers were purchased from Hangzhou Hanrui Building Materials Co., Ltd., with specifications of 0.2 mm in diameter and 14 mm in length.
[0022] Polycarboxylic acid water reducer (model: CA102) was purchased from Xi'an Jianda Hengyan Material Technology Co., Ltd., which is composed of multiple components such as polycarboxylic acid and its derivatives, additives and solvents; among them, polycarboxylic acid and its derivatives are the main components of water reducer, and its chemical structure is a polymer compound containing carboxylic acid functional groups and polyoxyethylene side chains. These polymer compounds can promote the dispersion and fluidity between cement particles by forming physical or chemical adsorption on the surface of cement particles, thereby achieving the effects of reducing the water-cement ratio of concrete, increasing the strength of concrete, and improving the working performance of concrete.
[0023] The defoaming agent is specifically an organosilicon defoaming agent (model: DF-2854), purchased from Yang's Chemical.
[0024] Other materials used in the present invention, if not otherwise stated, can be obtained through commercial channels. Other terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The present invention is further described in detail below in conjunction with specific examples and with reference to data. The following examples are only for illustrating the present invention, and are not intended to limit the scope of the present invention in any way.
[0025] Example 1
[0026] The preparation steps of modified shaped copper-plated steel fiber are as follows:
[0027] (1) Structural shaping
[0028] The copper-plated steel fiber is placed in a wave-shaped forming mold, and the middle part of the copper-plated steel fiber is made into a wave shape by mechanical processing. Then the wavy copper-plated steel fiber is hot-forged, and the two ends are forked, and the two ends are separated to form a forked structure to obtain a shaped copper-plated steel fiber. Its shape is wavy in the middle and forked at both ends. Figure 1 As shown:
[0029] (2) Surface modification
[0030] Use warm water and neutral detergent to remove dust and stains on the surface of the copper-plated steel fiber, and then use alcohol to degrease the shaped copper-plated steel fiber to remove surface impurities and pollutants to ensure a clean surface. Then soak the clean and dry shaped copper-plated steel fiber in a 65% phosphoric acid solution for 2 months and dry it to obtain a modified shaped copper-plated steel fiber.
[0031] In the present invention, the copper-plated steel fiber is structurally shaped to increase the bonding force and tensile strength between the copper-plated steel fiber and concrete.
[0032] In the present invention, phosphoric acid in the phosphoric acid solution can react with the metal copper ions on the surface of the copper-plated steel fiber to form a phosphate layer, namely copper phosphate Cu3(PO4)2, which can improve the bonding force between the copper-plated steel fiber and concrete. The phosphate layer can increase the roughness of the surface of the copper-plated steel fiber and increase the surface energy, thereby increasing the mechanical bonding force and chemical bonding force between the copper-plated steel fiber and concrete, thereby greatly improving the bone-holding force of the copper-plated steel fiber in UHPC.
[0033] The reaction formula is 3Cu+2H3PO4→Cu3(PO4)2+3H2
[0034] In this reaction, phosphoric acid reacts with copper ions on the surface of copper-plated steel fibers to generate copper phosphate and hydrogen. Copper phosphate forms a film with a certain degree of roughness and good bonding properties on the surface of copper-plated steel fibers. When the copper-plated steel fibers come into contact with the cement matrix in concrete, this film can chemically react or physically adsorb with the cement matrix. The rough steel fibers help to form a strong bond, thereby greatly improving the bone-holding strength of copper-plated steel fibers in UHPC (ultra-high performance concrete).
[0035] 1. Performance Testing
[0036] The modified shaped copper-coated steel fiber was mixed with UHPC (ultra-high performance concrete) to prepare UHPC specimens. The formula is shown in Table 1:
[0037] Table 1
[0038]
[0039]
[0040] The specific method for preparing UHPC specimens is as follows:
[0041] Mixing: Mix all materials evenly according to the designed proportions in Table 1 to ensure that the mass fraction and mixing ratio of each component meet the requirements.
[0042] Mixing: Pour the mixed materials into a blender, add appropriate amount of water, and mix thoroughly until a uniform mixture is obtained.
[0043] Pouring: Pour the mixed concrete into the pre-prepared cubic moulds, with each layer not exceeding 15cm in height. Compact the UHPC in the moulds, making sure there are no voids or bubbles.
[0044] Curing: Cover the mold with plastic film and place it in a constant temperature and humidity environment for curing. Depending on the specific experimental requirements, natural curing or steam curing can be used.
[0045] Demoulding: After the concrete is completely solidified, the mould is disassembled and the mould is gently tapped to release the specimen from the mould. The specimen is then placed in water and soaked for 28 days to reach the final strength.
[0046] The following test groups were set up: (1) the copper-plated steel fibers in the specimen did not change shape and were not subjected to surface modification (phosphoric acid treatment); (2) the copper-plated steel fibers in the specimen did not change shape but were subjected to surface modification; (3) the copper-plated steel fibers in the specimen only changed shape and were not subjected to surface modification; (4) the copper-plated steel fibers in the specimen both changed shape and were subjected to surface modification. The shaping and surface modification treatments are as shown in the above-mentioned Example 1.
[0047] The performance of UHPC specimens was tested according to relevant standards, as follows:
[0048] 1. Compressive strength test
[0049] The compressive strength is tested according to GB / T 50081-2019 standard.
[0050] Prepare a cubic UHPC specimen with a size of 100mm×100mm×100mm. Ensure that the surface of the specimen is smooth and has no obvious defects. Place the specimen on the loading platform of the compression tester and adjust the loading speed and maximum load of the tester. Apply a constant velocity pressure perpendicular to the specimen and gradually increase the load until the specimen is destroyed. Record the stress and strain data of the specimen under different loads and calculate the stress-strain curve. According to the stress-strain curve, determine the compressive strength of the UHPC specimen.
[0051] 2. Bending strength test
[0052] The bending strength is tested according to T / CECS 10107-2020 standard.
[0053] Prepare a standard-sized beam specimen with dimensions of 100mm×100mm×400mm. Ensure that the specimen surface is smooth and has no obvious defects. Place the specimen on the support of the flexural testing machine and adjust the loading speed and maximum load of the testing machine. Apply a constant-speed bending load perpendicular to the plane of the specimen, and gradually increase the load until the specimen is destroyed. Record the deflection and load data of the specimen under different loads, and calculate the stress-deflection curve. According to the stress-deflection curve, determine the flexural strength of the UHPC specimen.
[0054] 3. Tensile strength test
[0055] The tensile strength is tested according to T / CECS 10107-2020 standard.
[0056] Prepare a standard-sized beam specimen with dimensions of 78mm×52mm×25mm. Ensure that the surface of the specimen is smooth and has no obvious defects. Adjust the parameters of the testing machine: According to the standard requirements, adjust the loading speed of the testing machine to 0.3mm / min and set the maximum load. Apply pressure: Before starting the test, apply a constant-speed pressure perpendicular to the specimen to eliminate relaxation and defects in the specimen. During pressure loading, gradually increase the load until the predetermined value. Stress loading: After pressure loading is completed, tensile loading begins. According to the test requirements, use the constant-speed loading method, that is, load the specimen at a constant rate until the specimen is destroyed. The loading rate is 0.3mm / min. Record data: During the test, record the load and displacement of the specimen. Data can be collected through sensors on the testing machine or external measuring equipment. Analyze the results: After the test is completed, draw a stress-strain curve based on the test data, and calculate the tensile strength and other mechanical properties of UHPC.
[0057] The test results are shown in Table 2:
[0058] Table 2 Mechanical properties experimental data
[0059]
[0060] It can be seen from Table 2 that after the copper-coated steel fibers were shaped and surface modified, the prepared UHPC concrete had significant improvements in tensile strength, compressive strength and flexural strength.
[0061] In summary, the present invention improves the bonding force between steel fibers and concrete, and increases the tensile strength (which can characterize the bone holding force), durability and crack resistance of UHPC by copper plating, shaping and surface modification of steel fibers.
[0062] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing modified and shaped copper-plated steel fiber, characterized in that: Here are the steps: The steel fiber is copper plated; the copper plated steel fiber is then structurally shaped so that the middle part is wavy and the two ends are forked; the shaped copper plated steel fiber is then immersed in a phosphoric acid solution, and after the immersion is completed, it is dried to obtain a modified shaped copper plated steel fiber; The structural shaping is to make the middle part of the copper-plated steel fiber present a wave shape through mechanical or hydraulic processing; and to form a bifurcated structure at both ends of the wave-shaped copper-plated steel fiber through welding, cold forging or hot forging; The concentration of the phosphoric acid solution is selected from 10 to 85%; and the soaking time is selected from 1 to 3 months.
2. The modified and shaped copper-plated steel fiber prepared by the method of claim 1.
3. Application of the modified shaped copper-plated steel fiber according to claim 2 in the preparation of high-grip UHPC concrete.
4. A UHPC concrete, characterized in that: It is composed of the following ingredients by mass: 40-80 parts of cement, 2-8 parts of modified plastic copper-plated steel fiber, 2-7 parts of kaolin, 2-10 parts of silica fume, 30-50 parts of quartz sand, 0.1-0.4 parts of polycarboxylic acid water reducer, and 0.1-0.6 parts of defoamer; The modified and shaped copper-plated steel fiber is the modified and shaped copper-plated steel fiber described in claim 2.
5. The UHPC concrete according to claim 4, characterized in that: The UHPC concrete is composed of the following components by mass: 60 parts of cement, 5 parts of modified plastic copper-plated steel fiber, 5 parts of kaolin, 4 parts of silica fume, 42 parts of quartz sand, 0.2 parts of polycarboxylic acid water reducer, and 0.2 parts of defoaming agent.
6. The UHPC concrete according to claim 4 or 5, characterized in that: The cement is selected from P.O52.5 silicate cement; the length of the copper-plated steel fiber is selected from 10~25mm; the particle size of the kaolin is selected from 300~500 mesh; the silica fume is selected from nano-grade silica fume; the quartz sand is composed of the following three particle sizes of quartz sand: 10 parts of 10~20 mesh quartz sand, 16 parts of 20~40 mesh quartz sand, and 16 parts of 40~70 mesh quartz sand; the polycarboxylate water reducer is selected from one or more of carboxylic acid type polycarboxylate water reducer, sulfate type polycarboxylate water reducer, and hydroxyphosphate type polycarboxylate water reducer; the defoamer is selected from one or more of silicone defoamers, nonionic surfactant defoamers, and anionic surfactant defoamers.